Embodied Social Proxy: Connecting Hub-and-Satellite Teams - Venolia, Gina; Tang, John; Cervantes, Ruy; Bly, Sara; Robertson, George; Inkpen, Kori; Drucker, Steven; Lee, Bongshin (Proceedings of CSCW 2010, 2010)
Current business conditions have given rise to a particular kind of distributed team that is mostly collocated except for one remote member. These “hub-and-satellite” teams face the challenge of leaving the satellite colleague out-of-sight and out-of-mind. We developed a telepresence device, called an Embodied Social Proxy (ESP), which represents the satellite worker in collaborations with hub colleagues. ESP serves as a consistent video conferencing terminal for the satellite that can be moved to wherever meetings occur. Our studies of teams using ESP in their daily work show that its continuous physical presence improved the interpersonal connections between hub and satellite colleagues.
This abstract and video were part of the CSCW 2010 Video program.